Computer science education and K-12 students’ computational thinking: A systematic review - Lee, Sang Joon; Francom, Gregory M.; Nuatomue, Jeremiah (International journal of educational research, 2022)
•This systematic review examined how CS education was implemented in schools and its efficacy for developing students’ computational thinking (CT).•Although educational interventions have not always been successful in CS education, this review provides strong evidence that overall, CS education promotes the development of students’ CT in the K-12 setting while improving their creative and critical thinking skills.•When integrated into other subjects, CS education increases students’ motivation, commitment, participation, and interest in the subject matter.•We recommend early access to CS education, various innovative instructional approaches to CS education and appropriate support and guidance for student learning. Also, there is a need for professional development opportunities for CS educators. This systematic review examined how computer science (CS) education was implemented in schools and its efficacy for developing students’ computational thinking (CT). Sixty-six papers were selected for this systematic review and analyzed for patterns in relation to the implementation of CS education in K-12 schools and its impact on the development of students’ CT skills. Although educational interventions have not always been successful in CS education, this review provides strong evidence that overall, CS education promotes the development of students’ CT in the K-12 setting while improving their creative and critical thinking skills. We recommend early access to CS education, various innovative instructional approaches to CS education and appropriate support and guidance for student learning.